Dhūmaketu - Kāśikara, Es. Em. (Manoramā Prakāśana, 2009)
Mumbaīcā kubaḍā āṇi pisāṭa māthephirū – Lāla viñcū – Ṭi.Bī kilara Ḍô. Sūryakānta Novelettes based on Dhumketu, a fictional male character
Novelettes. - Marathi in Devanagari-Schr
Keywords: Marathi fiction